Analysis of flood risk based on WMS model in urban catchment area Case study: Damand basins, Golabdareh and Saadabad, Tehran metropolitan area - amir safari; ali ahmadabadi; zahra sedighifar (تحقیقات کاربردی علوم جغرافیایی)
Flood plains and adjacent rivers, which, due to their particular circumstances, are considered suitable places for carrying out economic and social activities, are always subject to the dangers of flood events. Hence, in these areas, determination of flood progression and its elevation relative to the surface of the earth, as well as determining the characteristics of the flood during the various return periods, which will be called flood zoning, will be of great importance. In this regard, this research aims at integrating the WMS hydrologic model with ARC GIS software to estimate flood zones in the Damand, Goladdareh, Saadabad and Maghsoud Baik watersheds on the main river of Darband. At first, the river Darband was divided into 19 main sections and in the HEC-RAS model, the river was zoned. In this research, using different digital maps, the flood extent in the riverside lands was calculated for a flood with a return period of 2 to 500 years. The SCS method was also used to increase the accuracy and reliability and also to identify areas susceptible to runoff production. The results of the study show that, due to land use changes, especially in the river basin and the abundant construction of the studied basin, there is no flood control power.